“‘Little bags of remembrance’: du Maurier’s Peter Ibbetson and Victorian Theories of Ancestral Memory” - Vrettos, Athena (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractIn the late-Victorian period considerable speculation that dreams provided access to ancestral memories appeared in both literary and psychological texts. Psychologists and psychical researchers such as Thomas Laycock, Samuel Butler, and F. W. H. Myers, among others, conceptualized memories and dreams as social, rather than solitary, mental functions, capable of making trans-historical connections with other minds. Their theories of ancestral memory effectively challenged the boundaries of subjectivity and the singularity of selfhood by extending identity across generations. One of the most sensational and sustained explorations of ancestral memory was George du Maurier’s 1891 novel Peter Ibbetson, which simultaneously adopted, popularized and expanded this ongoing debate about the nature of memory and the evolutionary scope of the unconscious. This essay traces the various ways in which these discourses on ancestral memory intersect. Both echoing and anticipating writers in the newly emerging memory sciences, Du Maurier’s novel explores the central role of the senses in producing and retrieving involuntary memories and envisions the mechanisms of memory as akin to modern technologies such as photography and phonography. Du Maurier’s account of ancestral memory thereby dramatizes some of the most far-reaching questions in late-Victorian psychology about the relationship between memory, identity, and the material world.